Deficit funkce ruky u pacientů s Dupuytrenovou kontrakturou a průběh rekonvalescence po palmární fasciotomii - Trybus, M; Koziej, M; Bednarek, M; Brudnicki, J; Pokrowiecki, W (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2019)
PURPOSE OF THE STUDY To evaluate hand function deficiency in patients with Dupuytren's disease (DD) in addition to assessing the improvement of function after palmar fasciectomy by using different hand-related questionnaires. MATERIAL AND METHODS A total of 121 hands (95 patients) underwent surgery. Disease severity was designated using Tubiana's Staging System. The Tendency of changes of Disabilities of the Arm, Shoulder, and Hand questionnaire (DASH), Patient Evaluation Measure (PEM), and Hand Function Score (HFS) scores of patients with DD undergoing palmar fasciectomy were assessed prior to, 3 months after, and 1 year after the operation. Moreover, total loss of extension (TLoE) was evaluated using a goniometer in the same time intervals. Repeated measure ANOVA Friedman's test were used. Responsiveness to clinical change was calculated by using standardized response means (SRMs). RESULTS The results showed statistically significant improvement of the originally obtained questionnaire results after 3 months for DASH and HFS and 12 months for all forms; only the PEM and DASH score significantly changed between 3 and 12 months. TLoE before surgery was 144.1 o ±99.6 o ; 3-month and 1-year after surgery: 14.3 o ±58.0 o and 19.3 o ±34.7 o respectively. SRMs for 1 year after surgery was large for PEM (1.11) and medium for DASH (0.7) and HFS (0.79). CONCLUSIONS DASH, PEM, and HFS are valuable tools to monitor the hand function of patients with DD after surgery. Key words:hand function, Dupuytren's disease, palmar fasciectomy.
Keywords: fasciotomie; získané deformity ruky; průzkumy zdravotní péče; ukazatele zdravotního stavu; Hand; Health Care Surveys; Disability Evaluation; ruka; Recovery of Function; Humans; lidé; Dupuytrenova kontraktura; Hand Deformities, Acquired; obnova funkce; Dupuytren Contracture; Health Status Indicators; Fasciotomy; posuzování pracovní neschopnosti